Engineering gender, engineering the Jordanian State: Beyond the salvage ethnography of middle-class housewifery in the Middle East. (December 2022) - Hughes, Geoffrey F
The figure of the middle-class housewife or ' rabbat bayt ' emerged in the late 19th-century Arabic-language public sphere amidst the colonial encounter. This gendering of middle-classness responded to a perceived cultural 'lag' yet now itself increasingly signifies backwardness in relation to ideals of middle-classness emphasizing women's education and community service over older norms of purity and propriety. Today, amidst unemployment, discrimination, lack of childcare, lack of safe and reliable public transportation and a highly suburbanized built environment catering to male breadwinners, contemporary Jordanian families must navigate multiple class and gender paradigms. Against a tendency towards salvage ethnography that misrecognizes these constraints as manifestations of deeply held 'traditional' values, I emphasize their historicity, arguing that it is only by recognizing housewifery itself as a state project characteristic of the 20th century that we can appreciate how state-building projects drive the gendering of class roles – and the classing of gender roles.